2015
DOI: 10.4254/wjh.v7.i11.1494
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins in liver transplant patients: Perspectives of clinical immune modulation

Abstract: Shortage of appropriate donor grafts is the foremost current problem in organ transplantation. As a logical consequence, waiting times have extended and pretransplant mortality rates were significantly increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 175 publications
(344 reference statements)
0
15
0
Order By: Relevance
“…Our study aimed to evaluate the efficacy and safety of Cytotect®CP in patients with CMV infection after allo-HCT. In fact, hyperimmune anti-CMV polyclonal antibodies activity has been explained in other clinical settings by its ability to counteract the virus with high avidity antibodies and possibly through cellular immunological reaction modulation mediated by cytokines, Fab-mediated actions, targeting Fc receptors, interactions with dendritic cells, B and T cell implication, and intracellular signal transduction blockade [22,38,39]. Interestingly, other studies concluded that this treatment, applied after allo-HCT, reduced the risk of CMV infection from 62 to 36% and may be effective in such patients [23,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to evaluate the efficacy and safety of Cytotect®CP in patients with CMV infection after allo-HCT. In fact, hyperimmune anti-CMV polyclonal antibodies activity has been explained in other clinical settings by its ability to counteract the virus with high avidity antibodies and possibly through cellular immunological reaction modulation mediated by cytokines, Fab-mediated actions, targeting Fc receptors, interactions with dendritic cells, B and T cell implication, and intracellular signal transduction blockade [22,38,39]. Interestingly, other studies concluded that this treatment, applied after allo-HCT, reduced the risk of CMV infection from 62 to 36% and may be effective in such patients [23,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Although antiviral prophylaxis by ganciclovir or valganciclovir is nowadays widely established in patients with high-risk CMV immunoglobulin (Ig) G donor (D)/recipient (R) seroconstellation (D+/R−), this is usually not applicable in severely immunocompromised allograft recipients due to intolerance against common side effects like renal dysfunction, leukopenia and thrombocytopenia [11]. That is why anti-CMV hyperimmunoglobulin (CMVIg) for passive immunization is meanwhile increasingly reconsidered in selected patients [12]. Although tolerability and antiviral efficacies of CMVIg have clearly been confirmed in the past [13], its use is currently not a recommended standard for antiviral prophylaxis or treatment in the LT setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although tolerability and antiviral efficacies of CMVIg have clearly been confirmed in the past [13], its use is currently not a recommended standard for antiviral prophylaxis or treatment in the LT setting [14]. In recent years, there seems to be growing suggestive evidence that, apart from antiviral activities, CMVIg may provide anti-inflammatory and immunoregulatory properties that could be valuable to counteract CMV-related immune reactions [12,[15][16][17]. We hypothesized that critically ill liver recipients, who are particularly threatened by early inflammatory events, might benefit from these positive immunomodulatory capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence was related to the presence of pre-transplantation HBV DNA, which in the past has been detected using a hybridization methodology. To date, the mechanism of action of immunoglobulins in the setting of transplantation has not been completely elucidated [3,4]. They could neutralize the circulating virus, prevent its linkage to the receptor on the surface of the hepatocytes, or even block the production/secretion of HBs [3,4].…”
Section: Introductionmentioning
confidence: 99%